The Effect Of Compensation, Work Discipline, And Organizational Culture On Performance Of Employees In Pt Lahan Agro Inti Ketapang - Adinda Farah Salsabila; Andriyastuti Suratman (UNIVERSITAS PAKUAN, 2024)
This study aims to determine the effect of compensation, work discipline, and organizational culture on the performance of employees in PT Lahan Agro Inti Ketapang. It used a quantitative method by distributing questionnaires to 120 employees of PT Lahan Agro Inti Ketapang. The sampling technique used purposive sampling. The analysis tool used was SmartPLS 3.0 with the structural equation modelling (SEM) analysis method. The results of this study showed that compensation had no positive and significant effect on employee performance. While, both work discipline and organizational culture had a positive and significant effect on employee performance.